2022
DOI: 10.1111/head.14329
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes of internet searching suggest circannual rhythmicity of primary headache disorders

Abstract: Objective: To investigate whether web searching for headache disorders presents some circannual rhythm.Background: Studies support the influence of seasonal rhythms in primary headache disorders such as cluster headache (CH) and episodic migraine. We investigated whether internet users' searching for headaches reflect these circannual rhythms. Methods:This was an internet-based study using the Google Trends (Google) platform. The 10-year interest across four related topics (headache, migraine, tensiontype head… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…These migraineurs also reported interictal light hypersensitivity, ligh sure as a precipitating factor, and frequent use of sunglasses to prevent attacks [ other study showed that female migraineurs with aura had a marked seasonal va with more attacks during the light season [39]. A recent study using Google Trend that interest in headaches and migraine peaked in February, October, and Novem was lowest in July [40]. These studies suggest that many migraineurs may experie sonal variations in their headaches and that further study is required in clinical p…”
Section: Circadian and Circannual Rhythms In Migrainementioning
confidence: 99%
“…These migraineurs also reported interictal light hypersensitivity, ligh sure as a precipitating factor, and frequent use of sunglasses to prevent attacks [ other study showed that female migraineurs with aura had a marked seasonal va with more attacks during the light season [39]. A recent study using Google Trend that interest in headaches and migraine peaked in February, October, and Novem was lowest in July [40]. These studies suggest that many migraineurs may experie sonal variations in their headaches and that further study is required in clinical p…”
Section: Circadian and Circannual Rhythms In Migrainementioning
confidence: 99%
“…Such awareness for patients can inform the usefulness of various behavioral adaptations (even restrictions) that they may apply to themselves on a daily basis in order to mitigate "attack risk". Furthermore, Radziwon et al 8 looked at internet-user searching to confirm the clinical observation that some primary headache disorder activity (cluster and migraine) can be seasonal; hence, using public attention to the topic as a marker of disease prevalence.…”
mentioning
confidence: 99%
“…Furthermore, Radziwon et al 8 . looked at internet‐user searching to confirm the clinical observation that some primary headache disorder activity (cluster and migraine) can be seasonal; hence, using public attention to the topic as a marker of disease prevalence.…”
mentioning
confidence: 99%
“…4 The paper entitled "Seasonal changes of internet searching suggest circannual rhythmicity of primary headache disorders" by Radziwon and Waszak. 5 published in this journal edition brings an interesting example of how digital epidemiology can shed light into biological mechanisms.…”
mentioning
confidence: 99%